Impact of the Global Financial Crisis on the Gulf Cooperation Council Countries and Challenges Ahead : An Update - Khamis, May.; Senhadji, Abdelhak (Washington, D.C. : International Monetary Fund, 2010)
Departmental papers are usually focused on a specific economic topic, country, or region. They are prepared in a timely way to support the outreach needs of the IMF's area and functional departments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet